2007
DOI: 10.1177/0961203307084158
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis of microRNA expression in peripheral blood cells of systemic lupus erythematosus patients

Abstract: MicroRNAs (miRNAs) are noncoding RNA molecules of 21-24 nt that regulate the expression of target genes in a post-transcriptional manner. Evidence indicates that miRNAs play essential roles in embryogenesis, cell differentiation and pathogenesis of human diseases. This study describes a comparison between the miRNA profile of the systemic lupus erythematosus (SLE) patients and the controls to develop further understanding of the pathogenesis of SLE. Peripheral blood mononuclear cells were isolated from blood s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
233
2
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(245 citation statements)
references
References 37 publications
4
233
2
4
Order By: Relevance
“…The strong association between the miR-146a level and clinical disease activity indicates that it may serve as a new disease biomarker. Dai et al (42) recently identified several differentially expressed miRNA in lupus patients by microarray analysis; however, dysregulation of miR-146a was not reported. This is likely due to the difference between the quantification methods and patient cohorts used in their study as compared with ours.…”
Section: Discussionmentioning
confidence: 99%
“…The strong association between the miR-146a level and clinical disease activity indicates that it may serve as a new disease biomarker. Dai et al (42) recently identified several differentially expressed miRNA in lupus patients by microarray analysis; however, dysregulation of miR-146a was not reported. This is likely due to the difference between the quantification methods and patient cohorts used in their study as compared with ours.…”
Section: Discussionmentioning
confidence: 99%
“…By targeting the key signaling components, decreased levels of miR-146a lead to increased type I IFN pathway activity in lupus patients [16]. In addition, Dai et al [17] identified 16 miRNAs that are differentially expressed in SLE.…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%
“…Recently, aberrant expression of miRNAs was observed in patients with SLE [34][35][36][37] and murine models of lupus [38]. Therefore, miRNAs could regulate CD1d expression.…”
Section: Introductionmentioning
confidence: 99%